Facebook's Influence on Nepali Political Dynamics: Survey of Tribhuvan University Political Science Students in Nepal (Quest Journal of Management and Social Sciences, 2025)
Background: The growing influence of social media, particularly Facebook, on political awareness, engagement, and discourse among Nepali youth necessitates an examination of its impact. As political science students are key stakeholders in shaping future political narratives, understanding Facebook's role in their political behaviour is critical.Objectives: This study investigates how Facebook influences political views and activities among Political Science students at Tribhuvan University, focusing on algorithmic bias, micro-targeting, and political advertising. It also assesses the implications for democratic integrity.Methods: A quantitative approach was employed, with a structured questionnaire distributed to 230 students via stratified random sampling. Data analysis included descriptive and inferential statistics (correlation and regression) to test hypotheses.Results: Findings indicate a strong correlation between algorithmic bias and political dynamics (r = 0.853). Regression analysis revealed that algorithmic bias, micro-targeting, and social media participation collectively explain 86.1% of the variance in political behaviour. Risks like misinformation and polarisation were identified.Conclusion: Facebook significantly shapes political engagement among Nepali youth, underscoring the need for regulatory measures to mitigate risks and uphold democratic values. Future research should explore policy interventions and broader demographic impacts.Keywords: Algorithmic Bias, Micro-Targeting, Political Advertising, Social Media, Political Engagement, YouthPaper Type: Research PaperJEL Classification: D72, D83